Torres sineiras a Norte do Douro nos séculos XVII-XVIII (I) - Alves, Joaquim Jaime B. Ferreira (2014)
The present work is part of a study we want to do about the tower-bells located in northern Douro during the XVII th. and XVIII th. centuries. Their datation, formal analysis and situation in relation with the church, are some of our concerns. Due to the dimension of the chosen research area we decided to start this study by Vila Real and its limits; this was the reason why our research focused the church tower of São Domingos Convent, and the tower-bells of the churches of São João de Arroios and of São Martinho de Anta.